Spatial decomposition analysis of water intensity in China. (March 2020) - Zhang, Chenjun; Wu, Yusi; Yu, Yu
Abstract: The shortage of water resources has become a burning issue constraining China's sustained development with significant differences in water intensity among regions and provinces. Quantifying the driving effect of spatial differences in the country's water intensity is very important to the dual implementation actions of water resources and intensity in each region. Spatial analysis reveals the variations among regions, identifies contributing factors, and helps us to better understand the scope for improvement compared to temporal analysis. This paper constructs a Spatial Index Decomposition Analysis (S-IDA) model based on the conventional IDA model referenced in the literature and divides China into six regions according to The 13 th Five-Year Plan of Water-Saving Society Construction . We mainly examine the following four parts. First, the driving factors of the spatial difference of water intensity in the six regions are decomposed into intensity effect and structure effect. Second, we measure three industrial differences of the intensity effect and the structure effect in the six regions. Third, we decompose the drivers of the spatial differences of water intensity for provinces within the six regions into the intensity effect and the structure effect. Fourth, we select the results in 2015 to point out the key task of reducing water intensity in the six regions and in all provinces of those regions. The results underscore that each region should formulate and implement a sound water resource policy with differentiation and relevance according to actual conditions and provide a quantitative basis and support system so that regions can learn from each other about specific water-saving measures. These findings provide an insightful understanding of the spatial difference of water intensity and also a quantifiable justification for making building-specific water resources policies, which are discussed at the end of the study. Highlights: Spatial difference of water intensity in the six regions are decomposed into intensity effect and structure effect. Three industrial differences of the intensity effect and the structure effect in the six regions in China are measured. Spatial differences of water intensity for provinces in China are decomposed into intensity effect and structure effect.